1991
DOI: 10.1115/1.2919922
|View full text |Cite
|
Sign up to set email alerts
|

Crane Ship Response to Wave Groups

Abstract: The motion response of a shear-leg crane ship lifting a heavy load in wave groups was investigated. The 9-DOF dynamic model incorporated hull motions coupled with nonlinear large-angle load swing and elastic stretch of the hoisting rope assembly. Hydrodynamic response forces and wave excitation forces were taken to be frequency dependent, and nonlinear mooring system restoring forces were allowed for. Closed-form linearized results about the system equilibrium state verified our nonlinear simulation algorithm;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…A similar problem has also been investigated by Schellin et al in a later study [14], where using idealized wave groups they have shown that hook load response, when strongly coupled with ship motions, is mainly influenced by first-order wave-exciting forces. Jiang and Schellin [15] have developed another model to study the influence of nonlinearities arising from the mooring system and fluid viscosity.…”
Section: Introductionmentioning
confidence: 81%
“…A similar problem has also been investigated by Schellin et al in a later study [14], where using idealized wave groups they have shown that hook load response, when strongly coupled with ship motions, is mainly influenced by first-order wave-exciting forces. Jiang and Schellin [15] have developed another model to study the influence of nonlinearities arising from the mooring system and fluid viscosity.…”
Section: Introductionmentioning
confidence: 81%
“…The dynamic coupling between crane load and vessel motion was studied in Ref. [1] for a floating crane barge. The response of the barge was found when the barge and the crane are modeled as one rigid body.…”
Section: Introductionmentioning
confidence: 99%
“…The hook load consists of the weight of the deck structure, the weight of the rigging, external wind forces and dynamic loads caused by the dynamic motions of the crane vessel and transportation barge (Choo, et al 1993). The loads experienced by the transportation barge are wave-induced loads, the loss of structure weight by the lifting, and an impact load if the vertical motion of the barge relative to the deck structure is greater than the transient air gap between them (Cveticanin, 1995;Schellin, et al 1993).…”
Section: Introductionmentioning
confidence: 99%